The determinants of population self-control - Deborah A. Cobb-Clark; Sarah Christina Dahmann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
This paper demonstrates that structural factors can shape people's self-control. We study the determinants of adult self-control using population-representative data and exploiting two sources of quasi-experimental variation|Germany's division and compulsory schooling reforms. We find that former East Germans have substantially higher levels of self-control than West Germans and provide evidence for suppression as a possible underlying mechanism. An increase in compulsory schooling had no causal effect on self-control. Moreover, we find that self-control increases linearly with age. In contrast to previous findings for children, there is no gender gap in adult self-control and family background does not predict self-control.
Keywords: D90; C26; 330; determinants of self-control; quasi-experiments; German division; compulsory schooling reforms; population-representative evidence; Brief Self-Control Scale